Identifikasi Degradasi Tanah dan Pengaruh Faktor Penggunaan Lahan Terhadap Degradasi Tanah Pada Kebun Campuran Dan Semak Belukar Di Kecamatan Kairatu Kabupaten Seram Bagian Barat Propinsi Maluku - Silwanus M Talakua (JURNAL BUDIDAYA PERTANIAN, 2019)
Soil degradation on scrub is higer than the mixed planting with indicators of soil degradation are pedestal, root plant exposure, rill and gully. Individually, the extent of land use, the density of upper vegetation and the density of lower vegetation have significant effect on the soil degradation at mixed plantation and scrub. Simultaneously, the extent of land use, the density of upper vegetation and the density of lower vegetation have significant effect on the soil degradation at mixed plantation and scrub. The factors that has the greatest effect on the soil degradation at mixed plantation are the extent of land use and density of lower vegetation, att the scrub, those factors are the density of upper and lower vegetation. Key words: Soil degradation, the extent of landuse, density of upper vegetation, density of lower vegetation, mixed plantation and scrub. ABSTRAK Besar degradasi tanah pada semak belukar lebih tinggi dibandingkan kebun campuran dengan indikator degradasi tanah adalah pedestal, akar terekspos, alur dan parit. Secara tunggal, luas penggunaan lahan, kerapatan vegetasi atas dan kerapatan vegetasi bawah berpengaruh nyata terhadap degradasi tanah pada penggunaan lahan kebun campuran dan semak belukar. Secara serempak, luas penggunaan lahan, kerapatan vegetasi atas dan kerapatan vegetasi bawah berpengaruh nyata terhadap degradasi tanah pada penggunaan lahan kebun campuran dan semak belukar. Faktor yang paling berpengaruh terhadap degradasi tanah pada kebun campuran adalah luas penggunaan lahan dan kerapatan vegetasi bawah, sedangkan pada semak belukar adalah kerapatan vegetasi atas dan kerapatan vegetasi bawah. Kata Kunci: degradasi tanah, luas penggunaan lahan, kerapatan vegetasi atas, kerapatan vegetasi bawah, kebun campuran dan semak belukar.